Note regarding two bronze rings, recently dug up near Stobo Castle, Peeblesshire, the Seat of Sir Graham Montgomery (Proceedings of the Society of Antiquaries of Scotland, 1858)
Two bronze rings that were uncovered during road works near Stobo Castle were exhibited. The Fellows of the Society suggested that they were items of personal ornament that were buried alongside their owner.